Florida Plant Disease Management Guide: Beans - Shouan Zhang; Geoffrey Meru; Aaron Palmateer; Ken Pernezny (EDIS)
This fact sheet summarizes specific common diseases of beans, briefly describing symptoms and cultural controls. This edition is an update and revision with Geoffrey Meru as an added co-author.